The Inner Conflict of the Characters in the Novel Sisi Tergelap Surga and the Pedagogical Implications in Digital Modules in High School - Tiara Anisa Rahmah; Yulianeta; Welsi Damayanti (Raja Zulkarnain Education Foundation, 2026)
This study examines the inner conflicts of characters in Brian Khrisna's novel Sisi Tergelap Surga through Kurt Lewin's field theory and formulates their pedagogical implications for a digital module on character and characterization for Grade 12 students in Phase F. The study employed a qualitative descriptive method and a literary psychology approach. The novel served as the primary data source, while six characters with substantial psychological struggles were purposively selected: Juleha, Ujang, Danang, Resti, Sutikno, and Gofar. Data were collected through close reading and systematic note-taking of dialogue, narrated thoughts, actions, other characters' responses, and shifts in decision-making. The analysis mapped internal and external factors, objects of conflict, positive and negative valences, conflict types, and directions of resolution. The findings show that Juleha, Ujang, Resti, Sutikno, and Gofar experience approach—avoidance conflict, whereas Danang experiences avoidance—avoidance conflict. The different conflict centers indicate that personal needs, stigma, poverty, social acceptance, and self-interpretation create distinct valence configurations. These findings were integrated into a digital module through a sequence of activities that included recognizing the novel’s context, substantiating characterization with textual evidence, analyzing conflict and valence, and presenting interpretations through character-map infographics and critical responses. The study provides a framework for using literary psychology to deepen evidence-based character learning while remaining attentive to social context, empathy, and moral evaluation.